PENGARUH HARGA, KEPERCAYAAN DAN ADVERTISING (IKLAN) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKOPEDIA - Dwi Junita Anggila; Subandrio Subandrio (UM. Bengkulu, 2022)
This study aimed to determine the effect of price, trust and advertising toward purchasing decision consumers at Tokopedia. This study used descriptive research method with quantitative data analysis. The population of this study were all consumers in the community of the Selebar sub-district of Bengkulu City with a total of 80 respondents and sampling taken by using the accidental sampling technique. The data collection technique of this study used observation and questionnaire. The data analysis techniques used classical assumption test, multiple linear regression, coefficient of determination (R2), and hypothesis testing. The results of the study indicate multiple linear regression, the regression equation form Y = 2.480 + 0.746 (X_1) + 0.235 (X2) + 0.214 (X3). The results of the study and the hypothesis show that the price shows the value of t_hit>t_(α/2) (7.252 > 1.664) and (sig = 0.000 < 0.05), the confidence value shows the value of t_hit>t_(α/2) (2.718 > 1.664) and (sig = 0.000 < 0.05) and advertising shows the value of t_hit>t_(α/2) (2.031 > 1.664) and (sig = 0.000 < 0.05). Price (X1) is 7.252, trust variable (X2) is 2.718 and advertising variable is 2.031. The conclusion is based on the results of the research that has been done, there is a significant influence between the variables Price (X_1), Trust (X2) and Advertising (X3) together toward purchasing decisions of consumers on Tokopedia. Based on the finding above ca be concluded and suggested that consumers perceptions regarding the Price, Trust, Advertising factors from Tokopedia can be better and can be used as evaluation material and special concern from Tokopedia.in attemting to increase purchasig decision of their consumens. Keywords: Price, Trust, Advertising and Purchasing Decision. Consumers.